Studi Literatur Keanekaragaman Spesies Makroalga di Ekosistem Pantai Indonesia Dan Tingkat Pemahaman Tentang Protista Mirip Tumbuhan Tingkat SMA/MA - Aura Nazwari; Fadilah Pasaribu; Margareth Shanatasha Aritonang; Malem Karina Sinulingga; Naila Zahwa Sitompul; Najwa Huwaida Adenan; Syakila Anwar; Zhafira Khalisyah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
The diversity of macroalgae species in Indonesia's coastal ecosystems is important to understand and protect. Indonesia has a very long coastline and a variety of ecological conditions, from tropical to subtropical areas. This area provides a habitat that supports the growth of various macroalgae species. The method used is a qualitative research method analyzing the diversity of macroalgae species in Indonesian coastal ecosystems and the level of understanding of high school/MA level plant-like protists. Based on the research results, it can be concluded that the level of understanding of SMA/MA students about plant-like protists is still low. Students have difficulty distinguishing between protists and true plants